(3TeGeI GdYfHQ ajeG hQO aj GdgfO Yf SjO GdHTQs - (3ZdGe GRGO GdHdcQGejs
(3ChdgG (B:s
(3CeG HYO agPg GdfSNI hSeGg TeGeI GdYfHQ ajeG hQO ai GdgfO ef SjO GdHTQ QGLjkG ef GdMVQI GdQHGfjI s
(3BNQgG (B:s
(3HQLGd ef GdgfO hai QhGjI GdHNGQi JTHjgg GdNHGH GdehShj hGLYd di ef dOfc SdWGfkG fUjQkG hUd Gddge hSde Ydi fHjc hUajc hYdi Bdg GdcQGe hUMHg GdYXGe OGFekG CHOkG cKjQkG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B53s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
(3GdBUajI HMjOQ CHGO (B((3eLGejY (B41(28)) s
Keywords: (3GdJGQjNs